Estimating a Small Open-Economy Model for Egypt : Spillovers, Inflation Dynamics, and Implications for Monetary Policy - Arbatli Saxegaard, Elif (IMF Working Papers; Working Paper ;, 2011)
This paper estimates a small open economy model for Egypt to analyze inflation, output dynamics and monetary policy during 2005-2010. The interest rate channel is found to be relatively weak in Egypt, complicating the use of interest rates as the immediate target of monetary policy. However, the paper also finds a significant level of persistence in the policy rate, making monetary policy pro-cyclical. More active use of interest rate policy, measures to improve domestic debt markets and a gradual move towards inflation targeting can help support a successful disinflation strategy for Egypt.